Direct Introduction of an Alkylsulfonamido Group on C‐sites of Isomeric Dicarba‐closo‐dodecaboranes: The Influence of Stereochemistry on Inhibitory Activity against the Cancer‐Associated Carbonic Anhydrase IX Isoenzyme. Issue 69 (3rd November 2020) - Nekvinda, Jan; Kugler, Michael; Holub, Josef; El Anwar, Suzan; Brynda, Jiří; Pospíšilová, Klára; Růžičková, Zdeňka; Řezáčová, Pavlína; Grüner, Bohumír
Abstract: Carbonic anhydrase IX (CA IX), a tumor‐associated metalloenzyme, represents a validated target for cancer therapy and diagnostics. Herein, we report the inhibition properties of isomeric families of sulfonamidopropyl‐dicarba‐ closo ‐dodecaboranes group(s) prepared using a new direct five‐step synthesis from the corresponding parent cages. The protocol offers a reliable solution for synthesis of singly and doubly substituted dicarba‐ closo ‐dodecaboranes with a different geometric position of carbon atoms. The closo ‐compounds from the ortho ‐ and meta ‐series were then degraded to corresponding 11‐vertex dicarba‐ nido ‐undecaborate(1−) anions. All compounds show in vitro enzymatic activity against CA IX in the low nanomolar or subnanomolar range. This is accompanied by clear isomer dependence of the inhibition constant ( K i ) and selectivity towards CA IX. Decreasing trends in K i and selectivity index ( S I ) values are observed with increasing separation of the cage carbon atoms. Interactions of compounds with the active sites of CA IX were explored with X‐ray crystallography, and eight high‐resolution crystal structures uncovered the structural basis of inhibition potency and selectivity. Abstract : High‐resolution study : A new synthetic approach is introduced for the complete isomeric family of dicarba‐ closo ‐dodecaboranes which serve as highly potent inhibitors of tumor‐associated carbonic anhydrase IX.